Identifikasi Biologi Gurita dan Nilai Indeks Untuk Pengelolaan Perikanan di Kawasan Selat Alas Nusa Tenggara Barat - Muhammad Marzuki; Damai Diniariwisan; Wiwid Andriyani Lestariningsih (Postgraduate, University of Mataram, 2023)
Octopus is an important economic fishery commodity that has a high price and is a source of foreign exchange for the country, especially for fishermen in the West Nusa Tenggara region. The utilization status of the octopus fishery is not known yet and managed well for its purposes. This research aims to determine existing conditions, growth patterns, body shape, age group and condition factors, as well as to determine the index value and desired status of the biological dimensions of octopus fisheries management. The method used in this research is descriptive, where data is obtained from samples obtained from nature. The research results showed that the growth pattern of octopus caught in the waters of Alas Strait and landed on Ketapang beach, East Lombok Regency was negative allometric with a b value of 1.4516. Meanwhile, the octopus's body shape is in the less flat category with a condition factor (K) value of 1.91, with a length range between 25 cm - 60 cm. The status of stopping octopus management from the biological dimension obtained a value of 58.53% with quite sustainable status.Â